If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 36 + 2y + -15 = 12y + -9 + -5y Reorder the terms: 36 + -15 + 2y = 12y + -9 + -5y Combine like terms: 36 + -15 = 21 21 + 2y = 12y + -9 + -5y Reorder the terms: 21 + 2y = -9 + 12y + -5y Combine like terms: 12y + -5y = 7y 21 + 2y = -9 + 7y Solving 21 + 2y = -9 + 7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7y' to each side of the equation. 21 + 2y + -7y = -9 + 7y + -7y Combine like terms: 2y + -7y = -5y 21 + -5y = -9 + 7y + -7y Combine like terms: 7y + -7y = 0 21 + -5y = -9 + 0 21 + -5y = -9 Add '-21' to each side of the equation. 21 + -21 + -5y = -9 + -21 Combine like terms: 21 + -21 = 0 0 + -5y = -9 + -21 -5y = -9 + -21 Combine like terms: -9 + -21 = -30 -5y = -30 Divide each side by '-5'. y = 6 Simplifying y = 6
| 8-4+2R-4R+8R= | | 2L+2W=W+84 | | 8-r=3r-14 | | x-1b=72 | | .666h-9=6-.666h | | 8x+6y-10=0 | | 24b+4=52 | | (x-3)(x-4)-(x+4)=0 | | 2n^3-24n^2-23048n=0 | | 4.3+7.5=5.8 | | 10v^2=11v+6 | | -3-10=-46 | | -(12+2r)-(r+8)=-7r+3r | | 10U-2U= | | 6x^2-13x+4= | | 4.29b-0.692=11.749 | | 3[2(5x-7)-3(4x-6)]-4[5(x-1)-7x]=6[-4(x+2)+7x] | | 6+5(8w-9)= | | 36=2L+W | | 1w+5=4 | | 3-2(x-4)=2x-5 | | 3(4x+1)=3+12x-2 | | (X+10)+(4x-20)=90 | | 7R*2+8R+8R= | | 3x(.29)=3 | | 1y+-4x= | | 8v-18=26+3v | | 18+4(-4)= | | 50-40x=200 | | 3t-t=20 | | X^5-2x^4+x^3-x^2+2x-1=0 | | 50+40x=200 |